Предмет: Алгебра,
автор: Айви14
1)найдите значение выражения (х - 4b)(x^2 + 4xb + 16b^2) + 64b^3 + x^3 + b^2 при х=1 b=-2
Ответы
Автор ответа:
0
( x - 4b)( x^2 + 4xb + 16b^2) + 64b^3 + x^3 + b^2 =
= x^3 - 64b^3 + 64b^3 + x^3 + b^2 = 2x^3 + b^2
При x = 1 , b = - 2:
2x^3 + b^2 = 2*1 + (-2)^2 = 2 + 4 = 6
= x^3 - 64b^3 + 64b^3 + x^3 + b^2 = 2x^3 + b^2
При x = 1 , b = - 2:
2x^3 + b^2 = 2*1 + (-2)^2 = 2 + 4 = 6
Похожие вопросы
Предмет: Математика,
автор: liza83838383
Предмет: Информатика,
автор: Аноним
Предмет: История,
автор: andreiviper12
Предмет: Обществознание,
автор: annaegorova85